Somalis in the Twin Cities and Columbus Immigrant Incorporation in New Destinations - Chambers, Stefanie (Temple University Press, 2017)
Somalis in the Twin Cities and Columbus seeks to understand the integration outcomes of refugees in the Midwest at local and state levels to show how communities struggle with political, social, and economic incorporation. While many immigration titles examine the Latino community, this book focuses on the black Muslim Somalis, providing an important understanding of the lives of this understudied and misunderstood group--before and after their arrival to the U.S. It is a timely look at the American policies that help and hinder immigrants settling in the U.S.